Nitrogen‐Enriched Carbon/CNT Composites Based on Schiff‐Base Networks: Ultrahigh N Content and Enhanced Lithium Storage Properties. Issue 12 (19th February 2018) - Xiao, Zhichang; Song, Qi; Guo, Ruiying; Kong, Debin; Zhou, Shanke; Huang, Xiaoxiong; Iqbal, Rashid; Zhi, Linjie
Abstract: To improve the electrochemical performance of carbonaceous anodes for lithium ion batteries (LIBs), the incorporation of both well‐defined heteroatom species and the controllable 3D porous networks are urgently required. In this work, a novel N‐enriched carbon/carbon nanotube composite (NEC/CNT) through a chemically induced precursor‐controlled pyrolysis approach is developed. Instead of conventional N‐containing sources or precursors, Schiff‐base network (SNW‐1) enables the desirable combination of a 3D polymer with intrinsic microporosity and ultrahigh N‐content, which can significantly promote the fast transport of both Li + and electron. Significantly, the strong interaction between carbon skeleton and nitrogen atoms enables the retention of ultrahigh N‐content up to 21 wt% in the resultant NEC/CNT, which exhibits a super‐high capacity (1050 mAh g −1 ) for 1000 cycles and excellent rate performance (500 mAh g −1 at a current density of 5 A g −1 ) as the anode material for LIBs. The NEC/CNT composite affords a new model system as well as a totally different insight for deeply understanding the relationship between chemical structures and lithium ion storage properties, in which chemistry may play a more important role than previously expected. Abstract : A chemically induced precursor‐controlled pyrolysis approach is adopted as an efficient way to develop a novel N‐enriched carbon/carbon nanotube composite (NEC/CNT), where the strong interaction between carbon skeleton and nitrogen atoms enables the retention of ultrahigh N‐content up to 21 wt% in the resultant NEC/CNT even after heat‐treatment, which is demonstrated to be an excellent anode material for lithium ion batteries.